Atomic resolution HOLZ-STEM imaging of atom position modulation in oxide heterostructures - Nord, M; Barthel, J; Allen, CS; McGrouther, D; Kirkland, AI; MacLaren, I (Elsevier, 2021)
It is shown that higher order Laue zone (HOLZ) rings in high energy electron diffraction are specific to individual columns of atoms, and show different strengths, structure and radii for different atom columns along the same projection in a structure. An atomic resolution 4-dimensional STEM dataset is recorded from a <110> direction in a perovskite trilayer, where only the central LaFeO3 layer should show a period doubling that gives rise to an extra HOLZ ring. Careful comparison between experiment and multislice simulations is used to understand the origins of all features in the patterns. A strong HOLZ ring is seen for the La-O columns, indicating strong La position modulation along this direction, whereas a weaker ring is seen along the O columns, and a very weak ring is seen along the Fe columns. This demonstrates that atomic resolution HOLZ-STEM is a feasible method for investigating the 3D periodicity of crystalline materials with atomic resolution.